2000
DOI: 10.2307/3587739
|View full text |Cite
|
Sign up to set email alerts
|

L2 Literacy and the Design of the Self: A Case Study of a Teenager Writing on the Internet

Abstract: This article presents a case study that uses ethnographic and discourse analytic methods to examine how electronic textual experiences in ESL figure in the identity formation and literacy development of the learner. First, the article reviews some recent work in literacy studies, L2 learning, and computer‐mediated communication to provide a conceptual basis for studying discursive practices and identity formation in L2 learning. The results of a case study of a Chinese immigrant teenager's written corresponden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
267
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(289 citation statements)
references
References 30 publications
(17 reference statements)
3
267
0
4
Order By: Relevance
“…Some studies carried out in the 1960s and 1970s, such as Barrutia (1964and 1970), or Gilman (1969, already showed a tendency to study the effectiveness of a certain CALL application in language teaching. This was also one of the main foci in the 1990s and in more recent years, as we can see in Blake (2000), Cahill and Catanzaro (1997), Chun (1994), Chun and Plass (1996), Davis and Lyman-Hager (1997), Derwing, Munro, and Carbonaro (2000), clac 57/2014, 3-44 bilbatua and herrero de haro: attitudes 9 González-Edfelt (1990), González-Bueno (2000), Grace (2000Grace ( ), kasper (2000, Lam (2000), Nagata (1996Nagata ( , 1997Nagata ( , 1998Nagata ( , 1999, Osuna (2000), and Van Handle and Corl (1999), and more recently, in Aydin and Genç (2011), in Heift and Schulze (2012: 28), and Wang and Vásquez (2012).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Some studies carried out in the 1960s and 1970s, such as Barrutia (1964and 1970), or Gilman (1969, already showed a tendency to study the effectiveness of a certain CALL application in language teaching. This was also one of the main foci in the 1990s and in more recent years, as we can see in Blake (2000), Cahill and Catanzaro (1997), Chun (1994), Chun and Plass (1996), Davis and Lyman-Hager (1997), Derwing, Munro, and Carbonaro (2000), clac 57/2014, 3-44 bilbatua and herrero de haro: attitudes 9 González-Edfelt (1990), González-Bueno (2000), Grace (2000Grace ( ), kasper (2000, Lam (2000), Nagata (1996Nagata ( , 1997Nagata ( , 1998Nagata ( , 1999, Osuna (2000), and Van Handle and Corl (1999), and more recently, in Aydin and Genç (2011), in Heift and Schulze (2012: 28), and Wang and Vásquez (2012).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Lam (2000), also comments on this, saying that "teachers' lack of knowledge about using computers and lack of training for integrating computer technology into the classroom were related to their reluctance to use computer technology in the classroom".…”
Section: Teachers' Negative Attitudes Towards Call: Spainmentioning
confidence: 99%
“…The way that technology provides language learners with the means to construct imagined lives has been investigated by Lam (2000Lam ( , 2006, for example, who examined the computermediated transnational identities that immigrant youth in the USA were fashioning for themselves as multilingual, multicompetent actors. She found that these identities afforded them possibilities to provide language learning opportunities for themselves that were broader than those available to them in school, where they were stigmatized as immigrants and incompetent language users.…”
Section: Digital Technology Identity and Language Learningmentioning
confidence: 99%
“…Save for a few studies (Lam, 2000(Lam, , 2004Yi, 2005), there has been little inquiry into the roles of popular and fan culture in the online literacy and social practices of English language learning youth. Moreover, with the fast-paced propagation of new media and technologies, novel fan practices and 'virtual' communities based around popular culture seem to spring up on a daily basis.…”
Section: Introductionmentioning
confidence: 99%